2000
DOI: 10.1007/s001980070032
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplementation with Calcium-Rich Mineral Waters: A Systematic Review and Meta-analysis of its Bioavailability

Abstract: The relevance of calcium (Ca2+), an essential bone mineral, to the prevention and treatment of osteoporosis is well established. However, a good deal of evidence casts doubt on the validity of current RDAs (recommended daily allowance), i.e., 800-1000 mg/day. New guidelines consistently advocate higher daily intakes (up to 1500 mg/day), a goal that may be difficult to achieve for many patients. Environmental as well as individual behavioral factors may limit the consumption of dairy products, whereas calcium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 21 publications
1
41
0
8
Order By: Relevance
“…Skeletal health and bone mineralization need a regular calcium intake and calcic mineral waters represent an important dietary source of calcium and should be recognized as good low-calorie nutritional calcium supplements (43). The calcium bioavailability of mineral waters has been investigated by different Authors and it is demonstrated that calcium from mineral waters is bioavailable as dairy products, sometimes also more than milk (37,42). Moreover, calcium-rich mineral waters increase bone mineralization, considering both femoral and spinal bone mineral density after calcic waters intake (44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal health and bone mineralization need a regular calcium intake and calcic mineral waters represent an important dietary source of calcium and should be recognized as good low-calorie nutritional calcium supplements (43). The calcium bioavailability of mineral waters has been investigated by different Authors and it is demonstrated that calcium from mineral waters is bioavailable as dairy products, sometimes also more than milk (37,42). Moreover, calcium-rich mineral waters increase bone mineralization, considering both femoral and spinal bone mineral density after calcic waters intake (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and a meta-analysis on five studies shows that, although only a few studies with a relatively small number of subjects are available, the calcium bioavailability of mineral waters is at least comparable to, and possibly better than, that from dairy products or pharmaceutical preparations (42). Because of calcium bioavailability, high-calcium mineral waters represent an important dietary source of calcium and should be recognized as good low-calorie nutritional calcium supplements (43).…”
Section: "Calcic Mineral Waters"mentioning
confidence: 99%
“…Therapeutic, low volume consumption of highly mineralized waters has a great influence on the activity of the gastrointestinal system, ionic balance of the organism, and excretion. A series of clinical trials has been published on the preventive action of mineralized waters in several diseases (Worwood et al 1996;Rodgers 1997;Bohmer et al 2000). The everyday mineral water consumption of the population, however, can also be viewed as a preventive measure.…”
Section: Mineral Water Consumptionmentioning
confidence: 97%
“…In den meisten Studien wird die Bioverfügbarkeit von Calcium aus Mineralwässern mit jener aus Milch verglichen und festgestellt, dass die Werte der Bioverfügbarkeit aus beiden Getränken vergleichbar sind [2][3][4]. Böhmer et al fanden in einer Meta-Analyse 6 Studien die sich mit der Problematik der Calciumresorption aus Mineralwasser befassten [3].…”
Section: Bioverfügbarkeit Von Calcium Aus Mineralwässernunclassified